2010
DOI: 10.1097/psy.0b013e3181cb9377
|View full text |Cite
|
Sign up to set email alerts
|

Stress, Inflammation, and Yoga Practice

Abstract: Objective-To address the mechanisms underlying hatha yoga's potential stress-reduction benefits, we compared inflammatory and endocrine responses of novice and expert yoga practitioners before, during, and after a restorative hatha yoga session, as well as in two control conditions. Stressors before each of the three conditions provided data on the extent to which yoga speeded an individual's physiological recovery.Methods-50 healthy women (mean age=41.32, range=30-65), 25 novices and 25 experts, were exposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
193
5
6

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 283 publications
(208 citation statements)
references
References 42 publications
4
193
5
6
Order By: Relevance
“…Therefore, presence of mental disorders may lead to a maladaptive immune system in individuals [29]. Additionally, emotional states have been found to affect individuals' engagement in health-promoting behaviors [30,31]. Consequently, it is possible that individuals with a mental disorder are more likely to practice behaviors that are related to susceptibility to the common cold (i.e., less physical activity, poor sleeping habits, smoking).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, presence of mental disorders may lead to a maladaptive immune system in individuals [29]. Additionally, emotional states have been found to affect individuals' engagement in health-promoting behaviors [30,31]. Consequently, it is possible that individuals with a mental disorder are more likely to practice behaviors that are related to susceptibility to the common cold (i.e., less physical activity, poor sleeping habits, smoking).…”
Section: Discussionmentioning
confidence: 99%
“…Potentially, suffering from both conditions may increase neuroprogressive pathways and lead to worsening treatment outcomes, relapse or treatment resistance. Adjunct interventions that may be considered include the addition of anti-inflammatory drugs such as COX-2 inhibitors (Muller and Schwarz, 2008) and the TNF antagonist, infliximab (Raison et al, 2013), medications with neuroprotective properties (e.g., antidepressants, mood stabilisers) (Dodd et al, 2013, Malhi et al, 2012, herbs and nutrients with anti-inflammatory and antioxidant properties (e.g., curcumin, resveratrol, omega-3 fatty acids, green tea, n-acetyl cysteine, CoQ10, selenium, zinc, alpha lipoic acid and vitamins such as A, C and E) (Alappat and Awad, 2010, Floyd, 1999, Kim et al, 2008, Lopresti et al, 2012, Scapagnini et al, 2012 and lifestyle changes known to enhance neurogenesis (e.g., sleep hygiene interventions, meditation, yoga, relaxation therapies and exercise) (Doraiswamy and Xiong, 2007, Kiecolt-Glaser et al, 2010, Lopresti et al, 2013.…”
Section: Do Obese and Overweight Psychiatric Populations Require Specmentioning
confidence: 99%
“…It has been suggested that Yoga practices could reduce pro-inflammatory cytokine and increase anti-inflammatory cytokine and this beneficial effect has been primarily attributed to reductions in the stress levels [32,33]. A randomized controlled 3-month trial with 200 breast cancer survivors by Kiecolt-Glaser JK et al [34] reported that "Yoga practice substantially reduced fatigue and inflammation".…”
Section: Discussionmentioning
confidence: 99%